2018
DOI: 10.4067/s0717-95022018000100367
|View full text |Cite
|
Sign up to set email alerts
|

Rol del Consumo de Alcohol y Antioxidantes sobre la Metilación Global del ADN y Cáncer

Abstract: SANDOVAL, C.; VÁSQUEZ, B. SOUZA-MELLO, V.; MANDARIM-DE-LACERDA, C. A. & DEL SOL, M.Rol del consumo de alcohol y antioxidantes sobre la metilación global del ADN y cáncer. Int. J. Morphol., 36(1):367-372, 2018. RESUMEN:El alcoholismo es una enfermedad crónica recidivante asociada a disfunción psicológica, social y física. El alcohol no sólo es una droga adictiva, también produce alteraciones en las actividades y funciones de múltiples sistemas y órganos. Actualmente, diversos estudios demuestran que el ambiente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A positive relationship between ADH activity and leukocyte ascorbic acid concentration has been discovered in people with liver disease [69]. Furthermore, the acetaldehyde produced has been associated with ethanolinduced hepatotoxicity [70,71], and when paired with hepatic CYP2E1 activation, these factors enhance oxidative stress in hepatocytes [12,33,72,73]. On the other hand, vitamin C has been demonstrated to protect against the detrimental effects of acetaldehyde in animal experiments [74].…”
Section: Vitamin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive relationship between ADH activity and leukocyte ascorbic acid concentration has been discovered in people with liver disease [69]. Furthermore, the acetaldehyde produced has been associated with ethanolinduced hepatotoxicity [70,71], and when paired with hepatic CYP2E1 activation, these factors enhance oxidative stress in hepatocytes [12,33,72,73]. On the other hand, vitamin C has been demonstrated to protect against the detrimental effects of acetaldehyde in animal experiments [74].…”
Section: Vitamin Cmentioning
confidence: 99%
“…Vitamin E deficiency, according to earlier research, makes the liver more sensitive to alcohol [97]. In this sense, vitamin E has been demonstrated to have hepatoprotective characteristics in rat models, including membrane stability, reduced nuclear factor-kappa B activation, decreased TNF-α generation, and suppressed hepatic stellate cell activation [12,33,73,95].…”
Section: Vitamin Ementioning
confidence: 99%
“…Pancreatic acinar cells use both oxidative and nonoxidative pathways to metabolize alcohol [16][17][18]. In fact, previous studies have demonstrated that alcohol probably alters the class II alcohol dehydrogenase (ADH2) [19] and ADH3 isoforms [19,20] to inhibit acinar ethanol oxidation.…”
Section: Introductionmentioning
confidence: 99%